Inaktivasi Termal Spora Bacillus Licheniformis Dalam Jus Nanas - Dewi Sunarti; Evelyn Evelyn; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bacillus licheniformis is a bacteria that has high heat resistance. The purpose of this study was to determine the effect of temperature (T: 85 ° C, 90 ° C, 95 ° C) at soluble solid SS: 12 ° Brix on the thermal inactivation of B. licheniformis. Then determine the value of D andZ. This study uses the thermal method of pasteurization process and spore calculation using the spread plate method. The D-values obtained at SS 12 ° Brix for temperatures 85, 90 and 95 ° C were 16.56; 7.63; and 3.52 minutes and the Z-value obtained is in the at 14,88 ° C. Itwas shown that haiger temperature resulted in the decreasing of the time needed to inactivate the spores. The results of this study emphasize the importance of temperature to the D and Z value for pineapple juice pasteurization.Keywords: bacillus licheniformis, endospore, inactivation, pasteurization, pineapple juice.